G483(P) National survey of management during illness (sick–day) of type 1 diabetes in children and young people. (27th April 2015) - Soni, A; Agwu, JC; Wright, NP; Moudiotis, C; Kershaw, M; Edge, J; Drew, J; Ng, SM
Abstract : Aims: Adequate sick day management at home may reduce the risk of progression to diabetic ketoacidosis (DKA) and admission to hospital. The UK does not have a consensus guideline for sick day management advice to children and young people with Type 1 Diabetes. Children's diabetes services vary in their practice of education and advice in the use of urine or blood ketone monitoring during illness. The aim of this project was to look at the variation of management of diabetes during illness. Methods: A survey was conducted by the Association of Children's Diabetes Clinicians (ACDC) who sent out questionnaires to all units managing children and young people with Type 1 Diabetes including: local sick day management rules, out of hours diabetes support for families and information about the local diabetes service. Results: Table 1 90/127 (71%) of the units responded to the survey. There were 13 tertiary centres. Median number of children per service was 165 (range 73–450). The majority of units (96%) have a sick day management guideline in place. Conclusion: There was a wide variation in the practice of monitoring and advice given during illness. All guidelines advised increased doses of insulin during sick days but there was no consensus on how to calculate increased doses. There were also variations in the use of ketone testing and frequency on blood glucose monitoring. Some units still use urine ketone testing routinely. There is a need for evidence based National guidance to be in place.